Historical Reconstruction of Subpolar North Atlantic Overturning and Its Relationship to Density. Issue 6 (29th May 2022) - Roussenov, Vassil M.; Williams, Richard G.; Lozier, M. Susan; Holliday, N. Penny; Smith, Doug M.
Abstract: The connections between the overturning of the subpolar North Atlantic and regional density changes are assessed on interannual and decadal timescales using historical, data‐based reconstructions of the overturning over the last 60 years and forward model integrations with buoyancy and wind forcing. The data‐based reconstructions reveal a dominant eastern basin contribution to the subpolar overturning in density space and changes in the overturning reaching ±2.5 Sv, which are both in accord with the Overturning in the Subpolar North Atlantic Program (OSNAP). The zonally integrated geostrophic velocity across the basin is connected to boundary contrasts in Montgomery potential in density space. The overturning for the eastern side of the basin is strongly correlated with density changes in the Irminger and Labrador Seas, while the overturning for the western side is correlated with boundary density changes in the Labrador Sea. These boundary density signals are a consequence of local atmospheric forcing and transport of upstream density changes. In forward model experiments, a localized density increase over the Irminger Sea increases the overturning over both sides of the basin due to dense waters spreading to the Labrador Sea. Conversely, a localized density increase over the Labrador Sea only increases the overturning for the western basin and instead eventually decreases the overturning for the eastern basin. Labrador Sea density provides a useful overturning metric by its direct control of the overturning over the western side and lower latitudes of the subpolar basin. Plain Language Summary: The overturning in the subpolar North Atlantic is reconstructed from historical data over the last 60 years. These reconstructions are consistent with ongoing observational measurements confirming that the overturning is dominated by an eastern basin contribution from between Greenland and Scotland. This overturning response is strongly correlated with density changes in the Labrador Sea and Irminger Sea. The boundary density for the Irminger Sea provides a direct control of the overturning over the eastern side of the basin and similarly, the boundary density around the Labrador Sea directly affects the overturning over the western side of the basin. Model experiments are conducted using localized forcing, showing that a density increase over the Irminger Sea enhances the overturning over the entire basin, while a density increase over the Labrador Sea instead eventually decreases the overturning for the eastern basin through a southern influx of warmer and lighter water. Key Points: Dominant eastern basin contribution to overturning in reconstructions for the subpolar North Atlantic in accord with recent observations Boundary density changes in the Irminger Sea connect to overturning changes over the eastern subpolar basin Localized buoyancy forcing over the Labrador Sea only enhances the overturning changes over the western side of the subpolar basin